Dietary antioxidants for chronic periodontitis prevention and its treatment: a review on current evidences from animal and human studies - Alfonso Varela-López; Maurizio Battino; Pedro Bullón; José L. Quiles (Facultad de Farmacia, Universidad de Granada, 2015)
Objectives: Given the relationship between chronic periodontitis and high levels of oxidative stress, this review aims to clarify what role can played the dietary intake of different antioxidants in maintaining a healthy periodontium and in reducing chronic periodontitis risk, as well as possible use of dietary therapies based on them for this disease treatment. Methods: The database of the National Library of Medicine, Washington, DC (MEDLINE PubMed) was used and all the studies in animals and humans are on the subject of interest in English writing online available from inception of the database until May 2015 were collected. Results: Antioxidants analyzed in this regard include vitamin C, vitamin A, carotenoids and some polyphenols, and coenzyme Q; as well as minerals iron, copper and zinc that are constituents of antioxidant enzymes. Still, there is a paucity of studies with few human studies, mostly observational. Among the various antioxidants, vitamin E and polyphenols seem to have more evidence for its beneficial effect, but in general the studies are insufficient to rule out or establish what antioxidants are useful and which are not. Conclusions: Overall, the data presented indicate that dietary antioxidants are beneficial for periodontal health, at least under certain circumstances. However more studies are needed to establish the relationship between chronic periodontitis and each specific antioxidant and to design useful dietary interventions for this disease management.